MRI correlates of interaction between gender and expressive suppression among the Chinese population. (7th April 2017) - Wang, Kangcheng; Huang, Hui; Chen, Li; Hou, Xin; Zhang, Yong; Yang, Junyi; Hao, Xin; Qiu, Jiang
Highlights: Men showed higher scores in expressive suppression (ES) than women among the Chinese population. Cortical thickness analyses revealed a significant interaction between gender and ES in the superior frontal gyrus (SFG) A significant interaction between gender and ES was found within functional connectivity between SFG and regions of DMN. Abstract: Expressive suppression is a kind of emotion regulation strategies by suppressing behaviors related to emotional responding. Despite the amount of behavioral research on expressive suppression, the structural and functional mechanisms underlying the interaction between gender and expressive suppression in Chinese healthy subjects have remained unknown. In the current study, we assessed the levels of expressive suppression and acquired the structural and functional imaging data from 273 Chinese individuals. A nearly automatic cortical processing technique was used to calculate cortical thickness for each subject. The results from cortical thickness analyses revealed a significant interaction between gender and expressive suppression in the superior frontal gyrus. Then, we conducted the whole-brain functional connectivity analysis with the seed of the superior frontal gyrus to explore the functionally related regions of brain. Subsequent analysis of the interaction between gender and expressive suppression indicated a significant functional connectivity between the superior frontal gyrus and default mode network (DMN) core regions, including the medial prefrontal cortex, precuneus and parahippocampal gyrus. Our results provided the robust empirical evidence illustrating the role of the superior frontal gyrus and DMN in gender difference of expressive suppression among the Chinese population. These findings might have implications for understanding gender difference in emotion processing and regulation.